How do you factor 25b^2-60B+36?

Expert Answers

An illustration of the letter 'A' in a speech bubbles

Sorry... I forgot to do the Quadratic Formula method:

assume  `25B^2 -60B + 36 =0`

The Quadratic formula is

`B = (-b +- sqrt(b^2 - 4ac))/(2a)`  where a = 25, b = -60, and c = 36

`B = (60 +- sqrt(3600 - 3600))/(50) = 60/50 = 6/5`  so, putting this into factors:

 `(B - 6/5)(B-6/5) = (B - 6/5)^2 = (5B - 6)^2`

Approved by eNotes Editorial Team
An illustration of the letter 'A' in a speech bubbles

There are a couple of ways of factoring this polynomial.  Brute force and the Quadratic Formula.

By brute force, you need to find factors of 25 and of 36 that will combine to form -60.

Factors of 25                               factors of 36

1, 25                                           1, 36

5, 5                                             2, 18

                                                  3,  12

                                                  4,   9

                                                  6,   6

To get the signs to work our right, we would need for the factors to have subtraction.

Guess 1:

`(5B - 4)(5B - 9) = 25B^2 - 45B - 20B +36 = 25B^2 -65B +36`

Gues 2:

`(5B - 6)(5B -6) = 25B^2 - 30B - 30B + 36 = 25B^2 -60B + 36` as desired.

Approved by eNotes Editorial Team